A SECOND COURSE IN ACCOUNTANCY. - Hackett, Robt P. (The Accounting Review, 1933)
Abstract A second course in accountancy at the University of Illinois, in the United States, is offered to students who have had one semester of accounting fundamentals. These students are, for the most part, second semester freshmen. The text used is the second volume of "Elementary Accounting," which includes discussions and problems involving certain refinements of the first semester's work as well as many new subjects not touched upon previously. When this text was first introduced at the university several years ago it was used in the customary way. Text assignments were made and discussed, followed by the assignment and discussion of one or more disrelated problems on the particular material in hand. In such a course, the development could not be as logical as it had been in the most elementary course. In the first semester's work the student was continually forced to go over material which had been gone over earlier. Each step in the development of this first course depended very definitely upon all preceding steps.